New genus, new species and new records in Lamiinae (Coleoptera, Cerambycidae) - Pérez-Flores, Oscar; Santos-Silva, Antonio (Zootaxa, 2021)
A new genus and three new species of the subfamily Lamiinae are described and illustrated: Osckayia oaxacae gen. nov., sp. nov. from Mexico (Oaxaca); Pseudastylopsis albus sp. nov. from Mexico (Oaxaca) and Honduras (Cortés); and Urgleptes albomaculatus sp. nov. from Mexico (Oaxaca). New country record for Acanthoderes (Acanthoderes) giesberti Chemsak & Hovore, 2002 is provided.